2017
DOI: 10.1371/journal.pmed.1002300
|View full text |Cite
|
Sign up to set email alerts
|

Ebola exposure, illness experience, and Ebola antibody prevalence in international responders to the West African Ebola epidemic 2014–2016: A cross-sectional study

Abstract: BackgroundHealthcare and other front-line workers are at particular risk of infection with Ebola virus (EBOV). Despite the large-scale deployment of international responders, few cases of Ebola virus disease have been diagnosed in this group. Since asymptomatic or pauci-symptomatic infection has been described, it is plausible that infections have occurred in healthcare workers but have escaped being diagnosed. We aimed to assess the prevalence of asymptomatic or pauci-symptomatic infection, and of exposure ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
(42 reference statements)
0
24
0
Order By: Relevance
“…High risk was defined as definite exposure of mucous membranes or broken skin with the bodily fluids of a patient with EVD (eg, a needlestick injury through visibly soiled gloves). 3 Some HCWs became infected without a known exposure, raising further questions about the effectiveness of current PPE and PPE protocols. 4 The doffing process is believed to be a particularly high-risk time in terms of self-contamination and subsequent infection.…”
Section: Introductionmentioning
confidence: 99%
“…High risk was defined as definite exposure of mucous membranes or broken skin with the bodily fluids of a patient with EVD (eg, a needlestick injury through visibly soiled gloves). 3 Some HCWs became infected without a known exposure, raising further questions about the effectiveness of current PPE and PPE protocols. 4 The doffing process is believed to be a particularly high-risk time in terms of self-contamination and subsequent infection.…”
Section: Introductionmentioning
confidence: 99%
“…In this group of international responders returning from West Africa, 1 study participant appeared to have low-level reactivity that was not confirmed by other studies, and 1 study participant had reactivity that was not replicated on a different assay; all other providers (99%) tested negative. 20 As our study has demonstrated, HCP who received investigational EBOV vaccines may produce antibody responses against the EBOV proteins included in the vaccines. Some of our HCP had received EBOV vaccines expressing a single EBOV protein, GP.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, we analyzed the Ebolavirus membrane proteins which are NP, VP35, VP40, sGP, ssGP, VP30, and VP24 proteins. And the prediction of antigenicity of the non-identical sequences from membrane proteins were done with VaxiJen server [23] and TMHMM [24] prediction address used to identify exo-membrane amino acid sequence of specific protein. Antigenic B-cell epitopes predictions were done using BCPred and AAP prediction methods.…”
Section: Discussionmentioning
confidence: 99%